Do reduced visual acuity and refractive error affect classroom performance?. (22nd August 2019) - Hopkins, Shelley; Narayanasamy, Sumithira; Vincent, Stephen J; Sampson, Geoff P; Wood, Joanne M
Abstract : The role of visual acuity and refractive errors in the academic performance of children is controversial due to the variable quality of the research in this area and the mixed findings reported. This review aims to provide clarity by reviewing and critiquing relevant peer‐reviewed publications and also summarises what is known regarding the visual demands of modern classroom environments. The outcomes of this review suggest that while a number of studies have investigated the role of vision in relation to children's academic performances, the veracity of the evidence obtained from the majority of these studies is undermined by methodological limitations. Comparisons between studies are constrained by differences in experimental designs, instrumentation and sample characteristics. Despite these limitations, the weight of evidence suggests there is an association between academic performance and both visual acuity and refractive error in children. However, well‐designed experimental studies are necessary to further understand the relationship between these parameters.